2018
DOI: 10.1016/j.celrep.2018.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CDC25 as a Common Therapeutic Target for Triple-Negative Breast Cancer

Abstract: CDK4/6 inhibitors are effective against cancer cells expressing the tumor suppressor RB1, but not RB1-deficient cells, posing the challenge of how to target RB1 loss. In triple-negative breast cancer (TNBC), RB1 and PTEN are frequently inactivated together with TP53. We performed kinome/phosphatase inhibitor screens on primary mouse Rb/p53-, Pten/p53-, and human RB1/PTEN/TP53-deficient TNBC cell lines and identified CDC25 phosphatase as a common target. Pharmacological or genetic inhibition of CDC25 suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 58 publications
2
49
1
Order By: Relevance
“…Furthermore, it has been suggested that the FGF3 mediated RAS activation (Control #14) can lead to Vemurafenib resistance in melanoma cells [51]. Interestingly, inhibiting the CDC25 (Control # 9) family has been suggested as a potential therapeutic for triple negative breast cancer [28], and we see that knocking down CDC25A results in no proliferative steady states.…”
Section: Avoiding Proliferative Steady Statesmentioning
confidence: 58%
“…Furthermore, it has been suggested that the FGF3 mediated RAS activation (Control #14) can lead to Vemurafenib resistance in melanoma cells [51]. Interestingly, inhibiting the CDC25 (Control # 9) family has been suggested as a potential therapeutic for triple negative breast cancer [28], and we see that knocking down CDC25A results in no proliferative steady states.…”
Section: Avoiding Proliferative Steady Statesmentioning
confidence: 58%
“…Constant monitoring is essentially intended to assess resistance (Komarova & Wodarz, 2005) and reveal pathways to which tumors may become addicted during treatment (Luo, Solimini et al, 2009). CDC25 phosphatases are overexpressed in a variety of human cancers (Boutros et al, 2007, Kristjansdottir & Rudolph, 2004, are rate-limiting in tumorigenesis induced by Ras (Ray & Kiyokawa, 2008), and were recently proposed as target of choice in unresponsive, triple-negative breast cancer (Liu et al, 2018). In this study we set out to identify novel CDC25 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the recent discovery that CDC25 is the therapeutic target of choice in triple-negative breast cancers, namely those that are negative for estrogen-, progesterone-and HER2-receptor expression and that are unresponsive to standard therapy (Liu, Granieri et al, 2018), we set out to develop novel CDC25 inhibitors. To this end, we conducted a pharmacophore-guided drug discovery program that led to the identification of novel scaffolds of the naphthoquinone group displaying inhibition of CDC25 in enzymatic assays.…”
Section: Introductionmentioning
confidence: 99%
“…2d). Noteworthy, this analysis returned the CDC25B gene, known to be involved in breast cancer and being a potential therapeutic target 33 .…”
Section: H3k27ac Marks Across Tissues and Diseases H3k27ac Epigenetimentioning
confidence: 99%